Förintelselitteraturen och andra generationens överlevande - Ohlsson, Anders (Nordisk judaistik/Scandinavian Jewish Studies, 2000)
This article deals with Swedish Holocaust literature by and about the second-generation witnesses, e.g. the children of survivors. It focuses on three novels: Suzanne Gottfarb’s Systrarna Blaumans hemlighet [“The Secret of the Blauman Sisters”] (1987) and Susanne Levin’s Leva vidare [“Live on”] (1994) and Som min egen [“As my own”] (1996). The Holocaust is an integral part of the protagonists’ life and identity, although he or she has not personally experienced the event and in the article I examine three aspects of the conditions of life for the second-generation survivors. Firstly, their search for knowledge about their parents’ experiences. Secondly, the burden of this generation to carry and fulfil the expectations of their parents and thirdly their struggle with identity in a multi-cultural society, where identity not only stems from heritage.